Tradução e interpretação da libras/língua portuguesa no ensino superior: relatos de tradutores/intérpretes e alunos surdos. - Cardoso, Débora Uchôa Carneiro (2020)
Given the regulation of Law 12.319/10, which deals with the legitimation of the profession of Sign Language Translator/Interpreter, we are faced with some issues that permeate the exercise of this professional activity, and therefore needed to be better analyzed due to the high demand of this profession. At the moment when we are talking about an Interpreter, in the study that we set out to do, we deal with the inclusion of deaf people in Higher Education, a subject still little addressed in the academic field. Thus, the objective of this research was to analyze the performance of the professional in the exercise of this activity in Higher Education, through the report of themselves and deaf university students. We theoretically substantiate this study with Lacerda, Lopes, Pagura, Perlin, Quadros, and others. We employ the qualitative, descriptive methodology. We used as research instruments a semi-structured interview, as well as a script of observation of classes that were recorded in a field notebook. The results of this research showed that among the problems listed as those that may compromise the performance of the TILS, their formation and updating stand out as the most cited being endorsed by deaf students. The training promoted by the institutions for which they are working, associated with an individual search for a better knowledge of their activities, can minimize the effects of the gaps identified as generating difficulties in this service.